Studi Kasus Fenomena Tingkat Serapan Anggaran pada Satuan Kerja Perangkat Daerah - Perdana Kusuma Negara; Lilik Handajani; Lukman Effendy (Journal of Accounting and Investment, 2018)
This Study aims to identify factors causing the low absorption budget local government units (SKPD) especially in early year at Biro Umum Setda Provinsi  Nusa Tenggara Barat. To get deeply understanding and to find objective of research, this study uses qualitative method namely case study approach. In this study the authors emphasize on the point of view of individuals/actors who have experience in terms of financial management and disbursement of funds, not from the views of the organization. The results of this study provide an illustration that there are three factors affecting the absorption rate of the budget on Biro Umum Setda Provinsi  NTB after being identified using data analysis techniques from Miles and Huberman. Those dominant factors are policy, administratition and human resource. These three factors have a strong impact on the budget absorption rate which tends to be low in early year and as a result occur accumulation of budget in the end of the year.